Public Sector Financial Balances Based on the System of National Accounts - Pasynkov, Aleksey F. (Economy of Regions, 2021)
Studies on the impact of government expenditures on regional and municipal development mainly focus on examining local budgets. Simultaneously, each territory has various channels for financing public needs and collecting taxes and other payments. Therefore, this research develops and tests a methodology to construct the public sector financial balance at the municipal level. The presented approach in based on the System of National Accounts (SNA), which considers expenditures and revenues of the federal, regional or municipal budgets as a single institutional sector, regardless of their affiliation. Therefore, in order to achieve the municipal financial balance, it is necessary to analyse tax payments at various budget levels, grouping them in accordance with the SNA classification. For calculating municipal expenditures, an original technique was developed to consider the costs of all public sector financial flows, including direct federal and regional sources. We use official information on municipal payroll obtained from the Federal State Statistics Service database. The net lending/borrowing ratio is taken as a balance indicator of supply and use. Public sector financial balances were constructed for 69 municipalities of Sverdlovsk oblast. Calculations have shown that, on average, public sector expenditure is almost equally divided between regional and federal budgets (one half) and municipal budgets (another half). Various municipality types were identified: 9 donors of public administration resources in Sverdlovsk oblast; 5 territories (including Ekaterinburg city) with a moderate deficit of internal resources; 35 municipalities with a significant lack of finances; 11 areas completely dependent on public administration resources. This work is part of the research aiming to develop the System of Territorial Accounts, tat is, an SNA analogue that can be implemented at the regional and municipal levels.